Evaluating the effects of receive-only arrays in specific absorption rate simulations at 3 and 7T - Malzacher, Matthias; Davids, Mathias; Schad, Lothar R.; Chacón-Caldera, Jorge (Magnetic resonance imaging, 2018)
Specific absorption rate (SAR) simulations are performed for most clinical and research transmit coil configurations. Such simulations allow the determination of limits in transmit power for patient safety. Different human models and coil configurations have been previously investigated using these simulations. However, only a few works have accounted for the effect of the receive (Rx) arrays in the SAR calculations and they have used very specialized setups or simplified detuning modeling of the Rx elements. In this work, we performed electromagnetic simulations using a clinical alike setup for whole-body scans at 3T and head scans at 7T. SAR simulations are performed for both setups with and without Rx arrays. A difference below 10% percent was found for max SAR. The maximum difference for the mean SAR values of the 3T setups remained within 8% and within 15% of the 7T setup.
Available online 26 June 2018
Gesehen am 10.10.2019